Le recul stratégique : de l’anticipation nécessaire aux innovations juridiques - Marie-Laure Lambert (VertigO)
Climate change nowadays obliges to think about new legal tools to manage town planning on vulnerable coasts, in a context of the sea level rise. In case of public deficiency, the damages on buildings and persons will grow, as well as the risks of administrative or penal responsibility of public authorities. It is important to anticipate on this phenomenon, to build a law for the relocation of activities and possessions, which can be acceptable, sustainable and fair. The preservation or return to a more or less natural state of the most vulnerable shore line seems to be, in many cases, a means to guarantee the safety of persons, the protection and attractiveness of the inside spaces. The notion of " littoral public domain " could translate the legal status of these territories that will be gradually resumed by the sea. On this shoreline, the right must innovate to allow the withdrawal by the owners of the existing constructions, by integrating the long term: the spreading in the time of the loss of property and the introduction of social equity criteria are proposed. Finally, it can be convenient to undertake a reflection on the ways of living on the coast, as to imagine temporary, adaptable and more shared uses of this unstable space.